Association Mapping for 24 Traits Related to Protein Content, Gluten Strength, Color, Cooking, and Milling Quality Using Balanced and Unbalanced Data in Durum Wheat [Triticum turgidum L. var. durum (Desf).] - Johnson, Marina; Kumar, Ajay; Oladzad-Abbasabadi, Atena; Salsman, Evan; Aoun, Meriem; Manthey, Frank A.; Elias, Elias M. (Frontiers in Genetics, 2019)
Durum wheat [Triticum durum (Desf.)] is mostly used to produce pasta, couscous and bulgur. The quality of the grain and end use products determine its market value. However, quality tests are highly resource intensive and almost impossible to conduct in the early generations in the breeding program. Modern Genomics based tools like genome-wide association study (GWAS) coupled with high density single-nucleotide polymorphism (SNP) provides an excellent opportunity to genetically dissect complex quality traits to expedite cultivar development using molecular breeding approaches. This study used a panel of 243 cultivars and advanced breeding lines developed during the last 20 years to identify SNPs associated with 24 traits related to nutritional value and quality for marker-assisted durum wheat breeding. As a large amount of unbalance phenotypic data is generated every year on advanced lines in all the breeding programs, the applicability of such a dataset for identification of marker-trait-associations (MTAs) remains unclear. We observed that ~ 84% of the MTAs identified using an historic unbalanced dataset (belonging to a total of 80 environments collected over a period of 16 years), were also identified in a balanced dataset collected from two environments. This suggests the suitability of historic unbalanced phenotypic data to identify beneficial MTAs to facilitate local-knowledge-based breeding. In addition to providing extensive knowledge about the genetics of quality traits, association mapping identified several candidate markers to assist durum wheat quality improvement through molecular breeding. The molecular markers associated with the important traits could be extremely useful in the development of improved durum wheat cultivars using MAS.